Colonialism and the First HIV Epidemic - Wu, Jennifer (SFU Health Sciences Undergraduate Journal, 2023)
Since the HIV-1 pandemic began, 79 million people have been infected, and 36 million have died. While the origins of the HIV-1 pandemic are not widely known, research suggests that HIV originated in Kinshasa, the capital city of the former Belgian-Congo colony (Faria et al., 2014; Pépin, 2013). HIV was circulating within Africa for decades before its global spread. How did a virus originating from Africa spread globally? Evidence points to colonialism (Faria et al., 2014; Giles-Vernick et al., 2013; Pépin, 2013). Colonial influences on urbanization, social dynamics, and healthcare created conditions that favoured the early spread of HIV. Addressing the impacts of colonialism and its influence on the spread of HIV is critical, given the rise of infectious diseases such as COVID-19. Keywords: HIV epidemic, colonialism